A novel tooth surface modification method for spiral bevel gears with higher-order transmission error. (August 2018) - Mu, Yanming; Li, Wenli; Fang, Zongde; Zhang, Xijin
Highlights: The higher-order transmission error for high contact ratio spiral bevel gears. The function-oriented design based on ease-off. The auxiliary tooth surface correction motion with vertical offset and increment of machine centre to back modification. Abstract: To reduce the running noise and vibration of spiral bevel gears, we present a novel method for designing high-contact-ratio spiral bevel gears with the higher-order transmission error (HTE) based on the function-oriented design. According to the design HTE curve and contact path, the pinion target tooth surface can be acquired by correcting the conjugated tooth surface derived from the mating gear. We establish a mathematical model for the computerized numerically controlled cradle-style pinion generator with the following design parameters: tool parameters, initial machine settings, and polynomial coefficients of the auxiliary tooth surface correction motion. An optimal model was developed to solve for the polynomial coefficients. TCA and LTCA results show that the HTE spiral bevel gears designed with the auxiliary tooth surface correction motion meets the design requirements. The meshing quality of the HTE spiral bevel gears is also better than that of gears designed using the parabolic transmission error (PTE). The tooth surface correction method proposed in this paper can serve as a basis for modifying high-contact-ratio (HCR) spiral bevel gears.